Performance expectation fallout, knowledge search, and corporate dual innovation - Li Zheng; Yuanyuan Wang; Kang Fang (Heliyon, 2024)
How do firms determine their approach to dual innovation about performance expectations? This paper analyzes the decision-making process known as ''assessment-search-innovation'' that businesses use in response to performance feedback. Furthermore, the research investigates the function of knowledge search in the relationship between the gap in performance expectations and dual innovation. The study sample consists of 827 A-share high-tech firms from 2010 to 2022. Analyzed data from the car and input databases yield 2975 occurrences of imbalanced panel data. Utilizing Stata software for empirical research (Data analysis methods encompass descriptive statistics, correlation analysis, baseline regression analysis, robustness test, and endogeneity test), regression analysis revealed that the fallout of performance expectations stimulates firms' search for a wide range of knowledge and hinders their search for in-depth knowledge. In addition, there is a strong and positive correlation between the extent of knowledge sought and exploratory innovation. At the same time, the intensity of knowledge sought is also significantly and positively correlated with exploitative innovation. An investigation of the mechanism shows that the disparity in performance expectations impacts exploratory innovation by encouraging companies to search for a wide range of knowledge and impacts exploitative innovation by inhibiting companies from searching for in-depth knowledge. Moreover, it has been discovered that when companies face a decrease in their performance, they prioritize exploring a wide range of knowledge rather than focusing on in-depth knowledge. This is especially true when there is a high risk of bankruptcy or financial loss, in contrast to the low risk of bankruptcy or profit status. Moreover, it has been shown that doing a cross-industry search for knowledge enhances the positive correlation between searching for a wide range of knowledge and engaging in exploratory innovation. Similarly, searching for knowledge within the same sector amplifies the positive correlation between searching for in-depth knowledge and engaging in exploitative innovation. The study uncovers the inherent mechanism via which the disparity in performance expectations impacts the process of dual innovation by influencing information search. This paper offers theoretical justification and empirical proof for the process by which companies seek external knowledge and execute dual innovation strategies.